Authorship and memetization: a reflection on paratextualization of media products - Batista, Marilia; de Souza-Leão, André; Andrade, Taynãh; Silva, Bianca (Retail Management Review, 2023)
Objective: This work sought to reflect on the production of memes from the appropriation of pop culture objects, as a form of text authoring, which results in the paratextualization of these objects. Pop culture, although responsible for large market numbers, also implies cultural aspects, innovation and re-appropriation of its objects. This re-appropriation happens when we consider that the objects of the media industry are texts, because for the possibility of their consumption to exist, a certain degree of interpretation and involvement is required from the consumer. As texts, these objects are subject to paratexts, which are contents created based on a main object. In addition to this, the concept of authorship supports the statement that the creator of a text is not the best explainer and the only holder of its meanings, as the text carries within itself a limit of interpretive possibilities about it, which causes in the reader, receiver or consumer, the author-function, which positions them as subjects of the text in question. It is at the heart of active and critical participation that the prosuming subject takes an ideological stance and reaffirms his authorship, unveiling as continuous meaning relations in his production - the meme. Originality: From the understanding of the capacity of the text of memes and paratext by Gray et al., (2007), we rely on Foucault (2009) to highlight authorship as a functionality of its own discourse, the author-function presents itself in the possibility of reinterpretation of the reader, receiver or consumer, within the threshold of possibilities of the text itself. Main results: As research findings, we understand that the process of creating memes inspired by the pop culture objects represent a materialization of the authorial process of the appropriate text, thus resulting in the paratextualization performed by prosumers. Theoretical Contributions: The work theoretically contributes to studies on memetization, presenting its condition of paratext from Gray (2010), also dialoguing with concepts such as Foucault’s author-function (2009), which allows us to affirm that memes are species of prosumed paratexts. from an author-function, which allows other actors to be authors of a text.